2016
DOI: 10.1080/03009734.2016.1230157
|View full text |Cite
|
Sign up to set email alerts
|

PXL01 in sodium hyaluronate results in increased PRG4 expression: a potential mechanism for anti-adhesion

Abstract: PurposeTo investigate the anti-adhesive mechanisms of PXL01 in sodium hyaluronate (HA) by using the rabbit lactoferrin peptide, rabPXL01 in HA, in a rabbit model of healing tendons and tendon sheaths. The mechanism of action for PXL01 in HA is interesting since a recent clinical study of the human lactoferrin peptide PXL01 in HA administered around repaired tendons in the hand showed improved digit mobility.Materials and methodsOn days 1, 3, and 6 after tendon injury and surgical repair, reverse transcriptase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…PXL01 exhibits an inhibitory effect on the most important hallmarks of adhesion formation by repressing secretion of proinflammatory cytokines and promoting fibrinolysis (Nilsson et al, 2009). In addition, recent studies have shown that PXL01 regulates the production of the mucinous glycoprotein lubricin (Taguchi et al, 2009; Hayashi et al, 2013) in connection to surgery, which provides an additional mechanism to contribute to its adhesion-preventive properties (Edsfeldt et al, 2016). …”
Section: Amps As Therapeutic Agentsmentioning
confidence: 99%
“…PXL01 exhibits an inhibitory effect on the most important hallmarks of adhesion formation by repressing secretion of proinflammatory cytokines and promoting fibrinolysis (Nilsson et al, 2009). In addition, recent studies have shown that PXL01 regulates the production of the mucinous glycoprotein lubricin (Taguchi et al, 2009; Hayashi et al, 2013) in connection to surgery, which provides an additional mechanism to contribute to its adhesion-preventive properties (Edsfeldt et al, 2016). …”
Section: Amps As Therapeutic Agentsmentioning
confidence: 99%
“…Tenascin is found in abundance in tendons, both peri cellularly and around the collagen fiber bundles, and has been shown to be drastically upregulated upon injury. It has, furthermore, been postulated that the tenocytes respond to stress by producing Tenascin to increase the elasticity of the ECM surrounding them [ 32 ] and, through its effects, have anti-adhesive properties [ 33 , 34 ] at healing through blocking cell interactions with fibronectins and other matrix molecules [ 35 ]. The increased levels of Tenascin, and connected EGF-like and Fibronectin type-III domains in intra synovial tendon grafts compared to extra synovial grafts, may, therefore, play a role in anti-adhesive functions seen in intra synovial flexor tendon grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the mechanism of tendon injury showed that excessive load lead to the injury of tendon fibers, which would release a large number of inflammatory factors (35). With the continuous accumulation of inflammatory and collagen stimuli, the healing flexor tendon tissues secreted inflammatory cytokines such as IL-6, TNF-α, COX2, and IL-1β, and these cytokines promoted the accumulation of fibrin, and then lead to the formation of fiber adhesion (21,36). Inflammatory cytokines played a significant role in the process of tendon repair (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%